(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
In a globalized world, English language teaching (ELT) must extend beyond grammar and vocabulary to encompass cultural competence, a vital skill for effective intercultural communication. This article examines the importance of integrating cultural knowledge, awareness, and sensitivity into ELT curricula. It explores how embedding culture in language instruction enhances communicative abilities, fosters empathy, and promotes global awareness. Drawing on pedagogical models and classroom practices, the study outlines methods for incorporating cultural content through literature, media, and real-life tasks. Findings indicate that culturally responsive teaching strategies significantly boost student engagement and English proficiency, preparing learners for diverse academic and professional settings.